2016
DOI: 10.1038/srep35465
|View full text |Cite
|
Sign up to set email alerts
|

An anti-infective synthetic peptide with dual antimicrobial and immunomodulatory activities

Abstract: Antibiotic-resistant infections are predicted to kill 10 million people per year by 2050, costing the global economy $100 trillion. Therefore, there is an urgent need to develop alternative technologies. We have engineered a synthetic peptide called clavanin-MO, derived from a marine tunicate antimicrobial peptide, which exhibits potent antimicrobial and immunomodulatory properties both in vitro and in vivo. The peptide effectively killed a panel of representative bacterial strains, including multidrug-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 55 publications
0
61
0
Order By: Relevance
“…treatment with clavanin-MO showed an 80% survival rate. This correlates with a significant decrease (~8 logs) in the number of viable bacterial counts found in the peritoneal fluid of clavanin-MO-treated groups ( 67 ). This illustrates the ability of the antibacterial/immunomodulatory peptide to control inflammation and promote survival of the host following bacterial infection.…”
Section: Promoting Bacterial Clearance Through Modulating Host Inflammentioning
confidence: 87%
See 1 more Smart Citation
“…treatment with clavanin-MO showed an 80% survival rate. This correlates with a significant decrease (~8 logs) in the number of viable bacterial counts found in the peritoneal fluid of clavanin-MO-treated groups ( 67 ). This illustrates the ability of the antibacterial/immunomodulatory peptide to control inflammation and promote survival of the host following bacterial infection.…”
Section: Promoting Bacterial Clearance Through Modulating Host Inflammentioning
confidence: 87%
“…Alternatively, clavanin-MO, a synthetic peptide derived from clavanin A, demonstrated both host immune modulatory functions and direct antimicrobial activity against MDR strains of E. coli and methicillin-resistant S. aureus ( 67 ). In the cell-based study, clavanin-MO modulated immune responses by inducing anti-inflammatory cytokines (e.g., IL-10) and reduced LPS-mediated upregulation of proinflammatory cytokines (e.g., TNF-α and IL-12).…”
Section: Promoting Bacterial Clearance Through Modulating Host Inflammentioning
confidence: 99%
“…Other groups have used peptides to treat a variety of bacterial infections in animal models with varying levels of success. Silva et al treated mice infected with E. coli and S. aureus with peptides derived the marine tunicate Styela clava and found that a single dose of 10 mg/kg yielded survival rates of 80-90% [56]. In another study, it was found that a single 80-200 mg/kg dose boosted survival of rainbow trout infected with Yersinia ruckeri from 20% to 70% [57].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides provide immediately effective, non-specific defenses against infections through direct bactericidal activity or through indirect modulation of the host defense system by enhancing immune-responsive cells (29). Sublancin, produced by Bacillus subtilis 168, has been studied extensively for its antibacterial mechanisms (30, 31).…”
Section: Discussionmentioning
confidence: 99%